O reconhecimento do Estado palestino: origens e perspectivas - Baeza, Cecilia (Meridiano 47 - Journal of Global Studies, 2017)
The recent wave of South American recognition of a Palestinian state has drawn international attention. We will analyze the origins of the Palestinian Authority’s new diplomatic strategy in order to understand how Latin America has become a new relevant partner. We will then discuss the challenges of recognizing a Palestinian state by the United Nations, examining the positioning of the main actors.